Organizational culture types and individual readiness for change: evidence from Indonesia - Aktsar Hamdi Tsalits; Gugup Kismono (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study aims to examine the effect of organizational culture types on individual readiness for change in Indonesia as a country with high collectivism. Specifically, this study examines the effect of four types of culture namely clan, adhocracy, market, and hierarchy on individual readiness for change. The sample of this study was 264 employees of XYZ Company, a family company in Indonesia that made changes by releasing part of its shares into the stock market. Test results using simple regression support the hypothesis that clan culture and adhocracy have a positive effect on individual readiness for change. However, the influence of market culture and hierarchy on individual readiness for change was also found to be positive instead of negative as hypothesized. Discussions and suggestions for future research are presented.